Reaffirmation of Religious Intolerance And Inability of Justice In The Case of Apostle Paul Politics, Nepotism, Corruption And Neutrality - Adolfina Elisabeth Koamesakh; Iwan Setiawan Tarigan (LPPM IAKN Tarutung, 2021)
Human Rights Enforcement that has begun since the 17th century is increasing being fought in various parts of the world in this century. However, there are more and more injustices and human rights violations on the grounds of differences in beliefs. Conflicts between religious people often occur in religious societies including in democratic countries such as Indonesia in different scales of conflict and various forms of persecution, while the law often does not favor truth and justice. This research aims to raise the persecution experienced by the apostle Paul in the Book of Acts 24-26. The two angles highlighted in Paul's persecution are intolerance of belief and incompetence of legal justice. Intolerance of faith was committed by Jewish leaders. They demanded that Paul be put to death on charges of violating Jewish beliefs, the desecration of the Temple, the preaching of the remission of sins by Christ. Authorities and law enforcement failed to deliver justice and truth. Political interests, voice of majority, and mentality corrupt negate the personal human rights as free creatures. Apostle Paul shown his heroism in defending his faithful in Christ in front of the lawless persecutors. Indifferently from the king’s Agripa neutrality who knows the truth but he did not clear Paul's case to free him from being accused.